Isbat nikah terpadu sebagai solusi memperoleh hak identitas hukum - Ramdani Wahyu Sururie (State Institute of Islamic Studies (IAIN) Salatiga, 2017)
The integrated marriage isbat is a series of activity which is jointly conducted and coordinated withinparticular time and place between the Religious Court/Court of Law, the Regional Office of CitizenshipService in a city or a district, the sub-district Office of Religious Affairs with its mobile service for givingthe marriage legalization. The integrated marriage isbat is conducted based on the rules of the SupremeCourt, Number 1 in 2015. Even though the legal basis of such integrated marriage isbat is under therules of the Supreme Court, yet the function remains the same that is the regulatory function orregelende functie for the continuity of judicature implementation. The background of the issue of theSupreme Court Rules Number 1 in 2015 is that there are so many numbers of marriages which are notregistered because of the society’s lacking access to the courts. The aim of the integrated marriage isbatis to improve the access toward legal service and to help people, especially those who haves not, inobtaining the rights of marriage certificate, the excerpt of marriage certificate, and the birth certificate assimple, fast, and cheap as possible. Principally, the implementation of the integrated marriage isbat issimilar to the regular one conducted in the court; what make it different are that the place is outside thecourt, free of charge, single judge, and collective vacation. Therefore it can be concluded then that theimplementation of the integrated marriage isbat is to fulfill the rights in obtaining law identity for thosewho haves not as the solution for the law assurance.